2013
DOI: 10.1002/ana.23849
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacute direct thrombus imaging using computed tomography and gold nanoparticles

Abstract: This is the first report on a hyperacute direct thrombus imaging technique using thrombus-seeking AuNPs and computed tomography. When translated into stroke practice, the thrombus imaging may allow us to advance to personalized thrombolytic therapy by demonstrating thrombus burden, distribution, and character in a prompt and quantitative manner. Further study into this area is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…CT imaging was able to visualize plaques 30 minutes after induction of the thrombus and 5 minutes after injection of particles and also 48 hours and 3 weeks later without further injection of AuNP. Application of tissue plasminogen activator, the clinical preference for clot breakdown, led to a decrease in CT signal at the clot areas [69]. A follow-up study added fibrintargeting peptides to the formulation.…”
Section: Thrombus Targeted Goldmentioning
confidence: 99%
“…CT imaging was able to visualize plaques 30 minutes after induction of the thrombus and 5 minutes after injection of particles and also 48 hours and 3 weeks later without further injection of AuNP. Application of tissue plasminogen activator, the clinical preference for clot breakdown, led to a decrease in CT signal at the clot areas [69]. A follow-up study added fibrintargeting peptides to the formulation.…”
Section: Thrombus Targeted Goldmentioning
confidence: 99%
“…Furthermore, combining such systems with multicolor CT allowed distinguishing at once macrophages accumulation and calcification [71]. Glycol chitosan (GC) coating has also been demonstrated to enhance retention and compatibility of gold nanoparticles (Au-NPs) [72]. Furthermore, its affinity for fibrin makes it a coating of choice for thrombus targeting.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…The study showed that these nano particles allowed both the detection of primary and recurrent thrombi, and the monitoring the therapeutic efficacy of thrombolysis with tissue plasminogen activator (tPA). Due to a long circulating half-life, GC-gold nano particles remained available for entrapment into fibrin matrix for up to 3 weeks, allowing repetition or ongoing monitoring of thrombogenesis and thrombolysis (50). Given the need of rapid and reliable in vivo assessment of the thrombotic risk in patients with cardiovascular diseases in order to improve the diagnosis, risk stratification, and management of thrombotic syndromes, those systems represent a very attractive platform for use in clinical practice.…”
Section: Estimating the Burden Of Thrombosismentioning
confidence: 99%